A facile energy-saving route of fabricating thermoelectric Sb2Te3-Te nanocomposites and nanosized Te. Issue 10 (17th October 2018) - Liu, En-Yu; Lin, Fei-Hung; Yang, Zong-Ren; Liu, Chia-Jyi
Abstract : A facile energy-saving route is developed for fabricating Sb2 Te3 -Te nanocomposites and nanosized Te powders. The fabrication route not only avoids using organic chemicals, but also keeps the energy consumption to a minimum. The fabrication procedure involves two steps. Energetic precursors of nanosized powders of Sb and Te are produced at room temperature followed by hot pressing at 400°C under 70 MPa for 1 h. The resulting Sb2 Te3 -Te nanocomposite exhibits enhanced power factor. The dimensionless figure of merit zT value of the Sb2 Te3 -Te nanocomposite is 0.29 at 475 K.